2013
DOI: 10.2514/1.c031849
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of Low-Reynolds-Number Flow Over Thick and Thin NACA Airfoils

Abstract: In this study, the flowfields around NACA0012 and NACA0002 airfoils at Reynolds number of 23,000 and the aerodynamic characteristics of these flowfields were analyzed using implicit large-eddy simulation and laminar-flow simulation. Around this Reynolds number, the flow over an airfoil separates, transits, and reattaches, resulting in the generation of a laminar separation bubble at the angle of attack in a certain degree range. Over an NACA0012 airfoil, the separation point moves toward its leading edge with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 17 publications
10
41
0
Order By: Relevance
“…Refs. [6][7][8]. Therefore, a better understanding of the LSB characteristics is essential to prevent the unintended degradation of performance due to the LSB.…”
Section: Introductionmentioning
confidence: 98%
“…Refs. [6][7][8]. Therefore, a better understanding of the LSB characteristics is essential to prevent the unintended degradation of performance due to the LSB.…”
Section: Introductionmentioning
confidence: 98%
“…A number of large eddy simulations (LESs) of laminar separation bubble flows over flat plates and airfoils have been completed in recent years. [28][29][30][31][32][33] Recent work demonstrated that accurate large eddy simulations of laminar separation bubble flows are possible using only O(1%) of the resolution required by a DNS. 34 However, filtering was necessary to damp artifacts at the computational boundary between the implicit and explicit grids.…”
Section: B Motivationmentioning
confidence: 99%
“…The constant Smagorinsky model has been compared to its dynamic counterpart and a no-model case. 28 Other investigators relied entirely on the dynamic Smagorinsky model, 29,31,32 or on the implicit numerical dissipation of their chosen scheme as in implicit LES or ILES, 33 and in one case even without any prior knowledge of the dissipative scheme's effects on the resolved scales. 30 Without benchmark DNS data and a baseline case with no subgrid-scale model active to compare directly to, the performance of their implicit and explicit models could not be evaluated quantitatively.…”
Section: B Motivationmentioning
confidence: 99%
“…However, the magnitude of acoustic disturbances fed back into a boundary layer grows very rapidly as the inflow Mach number increases, which may cause reattachment via the development of an AFL, at the Reynolds number quite lower than 50, 000. In the numerical study conducted at Re = 2.3 × 10 4 and M = 0.2 [5], boundary-layer reattachment also occurs on an NACA0012…”
Section: Time-averaged Aerodynamic Forcesmentioning
confidence: 99%